Preformulation solid-state supramolecular beneficiation of selected active pharmaceutical ingredients and a novel drug candidate - Noonan, Terence James (Department of Chemistry, 2019)
The aim from the outset of the project on which this thesis is based was to make use of contemporary methods in the field of supramolecular chemistry to improve the suboptimal physicochemical properties of selected compounds for use in the formulation of pharmaceutical products. The compounds selected were: Clevudine, an established drug that is currently in use for the treatment of chronic hepatitis B infections, 6-(3- (Methylsulfonyl)phenyl)-3-(4-(methylsulfonyl)phenyl)-imidazo[1,2-b]pyridazine (MMV652103), a novel antimalarial drug candidate that displayed good in vitro potency against multidrug resistant and sensitive plasmodial strains and ()-α-lipoamide, a bioactive antioxidant that is currently in use for the clinical treatment of diabetic neuropathy and has other potential uses e.g. as an antiretroviral agent. The methods utilised in pursuit of novel solid-state forms of the compounds included a combination of crystal engineering and experimental screening for polymorphs, solvates/hydrates, cyclodextrin (CD) inclusion complexes, pharmaceutical salts and co-crystals. Screening involved grinding and co-precipitation methods. Characterisation of new forms involved thermal analytical methods including hot stage microscopy (HSM), differential thermal analysis (DTA), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and variable temperature powder X-ray diffraction (VTPXRD). In all cases where single-crystals of adequate quality and size were successfully prepared, the crystal structures were elucidated by single-crystal X-ray diffraction. Molecular conformations, inter- and intramolecular interactions and packing arrangements of crystals were characterised. Polymorphism of clevudine was addressed for the first time. Three polymorphs of clevudine were isolated and characterised in terms of crystal structures and thermal behaviour. The solubility and thermodynamic stability ranking of the three forms was established and schematic energy-temperature diagrams were constructed through the use of the thermal methods listed above, solvent-mediated transition experiments and by kinetic solubility experiments. Characterisation by infrared (IR) spectroscopy has made it possible to promptly and effortlessly identify each form. Multiple novel solid-state forms of the antimalarial drug candidate MMV652103 were produced including four polymorphs, a hydrate, five co-crystals and a salt. The solubility and thermodynamic stability ranking of the polymorphs was established through thermal analysis and kinetic solubility experiments. An amorphous form showed an improvement in dissolution rate, with a concentration 3-4 times that of the crystalline forms after one hour. The designation as co-crystals or salts was accomplished through the use of single crystal X-ray structural analysis and confirmed by IR spectroscopy. Stoichiometry was determined by 1 H - nuclear magnetic resonance (NMR) spectroscopy. A customised solubility experiment was carried out to compare the dissolution rates of the various multi-component forms of MMV652103 in an environment simulating the human duodenum. An enhancement of the dissolution rate was observed with a maximum concentration 4.7 times higher for the co-crystal than for the untreated active compound. Inclusion complexation of ()-α-lipoamide with native CDs (α-, β-, and γ-CD) was confirmed by comparison of putative PXRD traces with those of known isostructural series. Novel complexes were synthesised with the above mentioned native CDs as well as with three derivatised CDs (TRIMEA, DIMEB and TRIMEB). The crystal structures were characterised by single-crystal X-ray diffraction. Host-guest stoichiometries were determined by 1 H-NMR spectroscopy and validated by the ratio of mass loss through TGA. Water composition, melting points and thermal stability in terms of decomposition and guest loss temperatures of the complexes were determined by means of the appropriate thermal methods (DTA, TGA, DSC, HSM). Phase solubility experiments were carried out and showed solubility enhancements for the bioactive compound ranging from a 1.8 fold increase with α-CD to a 7.4 fold increase with randomly methylated β-CD.